Measuring judicial activism - Lindquist, Stefanie A., 1963-; Cross, Frank B. (Oxford : Oxford University Press, 2009)
'Measuring Judicial Activism' supplies empirical analysis to the widely discussed concept of judicial activism at the United States Supreme Court. The book seeks to move beyond more subjective debates by conceptualizing activism in non-ideological terms.
Description based on print version record.
Includes bibliographical references and index.
Keywords: United States. -- Supreme Court; Political questions and judicial power -- United States; Judicial review -- United States